Trends and hot spots in research on the prognostic value of gastric cancer biomarkers in the context of the Lauren classification: a bibliometric analysis - Nurbek Kozhakhmetuly Azbergenov; Talshyn Amirkhanqyzy Nurulla; Anar Balkashevna Tulyayeva; Saule Zhumabaevna Akhmetova; Nurgul Meirimovna Kereeva; Saltanat Nurslyamovna Akanova; Dinara Almatovna Zholmukhamedova (Frontiers in Medicine)
IntroductionModern research is aimed at finding reliable prognostic biomarkers. The Lauren classification remains an important tool for predicting outcomes in gastric cancer, especially when combined with certain biomarkers and tumor molecular characteristics. This study aims at quantifying the accumulated knowledge about the prognostic value of stomach cancer biomarkers in the context of the morphological Lauren’s classification, as well as providing recommendations for future studies.MethodsA literature search was conducted in the Scopus database in December 2024. The selection included 162 publications for the period 1995–2024. The analysis was performed using the statistical software RStudio, widely used in scientific research. The specialized Biblioshiny package was utilized for data analysis and visualization.ResultsThe average annual growth rate was 3.86%, and the average number of citations per article - 30.4, which underlines the high importance of the topic of the study. The largest number of publications originated from China (292 articles). Leading research institutions include Sungkyunkwan University School of Medicine (13 documents), Fudan University (12 documents), and Yonsei University College of Medicine (11 documents). The most prolific author is Zhang J., who conducted 13 studies in this field. The journal Pathology - Research and Practice holds the leading position with 8 publications. The most frequently occurring keyword is “gastric cancer” (94 mentions). Thematic trends include research on HER2 and microsatellite instability.ConclusionThe bibliometric analysis revealed the active development of research on the role of biomarkers in predicting gastric cancer prognosis based on Lauren’s classification. China is the leading country in this field, Sungkyunkwan University School of Medicine is the most active research institution, Zhang J. is the most influential researcher, Pathology - Research and Practice is the most productive journal. Current research focuses on HER2 and microsatellite instability.